The “best practices for farming” successfully contributed to decrease the antibiotic resistance gene abundances within dairy farms - Salerno, Barbara; Cornaggia, Matteo; Sabatino, Raffaella; Di Cesare, Andrea; Mantovani, Claudio; Barco, Lisa; Cordioli, Benedetta; Bano, Luca; Losasso, Carmen (Frontiers in Veterinary Science, 2025)
IntroductionFarms are significant hotspots for the dissemination of antibiotic-resistant bacteria and genes (ARGs) into the environment and directly to humans. The prevalence of ARGs on farms underscores the need for effective strategies to reduce their spread. This study aimed to evaluate the impact of a guideline on “best practices for farming” aimed at reducing the dissemination of antibiotic resistance.MethodsA guideline focused on prudent antibiotic use, selective therapy, and hygienic and immune-prophylactic practices was developed and provided to the owners of 10 selected dairy farms and their veterinarians. Fecal samples were collected from lactating cows, dry cows, and calves both before and after the implementation of the guideline. ARGs (blaTEM, ermB, sul2, and tetA) were initially screened by end-point PCR, followed by quantification using digital droplet PCR. ARG abundance was expressed in relative terms by dividing the copy number of ARGs by the copy number of the 16S rRNA gene.ResultsThe ARG abundances were higher in lactating cows compared to other categories. Despite similar levels of antibiotic administration (based on veterinary prescription data from the sampled farms) in both sampling campaigns, the total abundance of selected ARGs, particularly blaTEM and tetA, significantly decreased after the adoption of the farming guidelines.DiscussionThis study highlights the positive impact of prudent antibiotic use and the implementation of farming best practices in reducing the abundance of ARGs. The lactating cow category emerged as a crucial point of intervention for reducing the spread of antibiotic resistance. These findings contribute to ongoing efforts to address antibiotic resistance in farm environments and strengthen the evidence supporting the adoption of good farming practices.